Meneropong Peranan Kegiatan Keagamaan Dalam Mengurangi Bullying - Ummah, Risalul; Rahmawati, Cindy Agustin (Amaliyatu Tadris, 2025)
Bullying is a social phenomenon that is distressing and has the potential to harm individuals' psychological well-being. In an effort to reduce the level of Bullying, the role of religious activities becomes an important consideration. This article adopts a qualitative literature study approach to examine the role of religious activities in reducing Bullying. The results of the literature analysis indicate that religious activities have the potential to reduce Bullying through moral education, social support, self-control, forgiveness, peace, and responsible technology use. However, the effects may vary depending on contextual factors. This study highlights the need for further research in different contexts to understand the deeper role of religious activities in addressing Bullying. Bullying merupakan fenomena sosial yang meresahkan dan berpotensi merusak kesejahteraan psikologis individu. Dalam upaya untuk mengurangi tingkat Bullying, peran kegiatan keagamaan menjadi perhatian penting. Artikel ini mengadopsi pendekatan studi literatur kualitatif untuk meneropong peranan kegiatan keagamaan dalam mengurangi Bullying. Hasil analisis literatur menunjukkan bahwa kegiatan keagamaan dapat berpotensi mengurangi Bullying melalui pendidikan moral, dukungan sosial, pengendalian diri, pengampunan, perdamaian, dan penggunaan teknologi yang bertanggung jawab. Namun, efeknya dapat bervariasi tergantung pada faktor-faktor kontekstual. Studi ini menyoroti perlunya penelitian lebih lanjut dalam konteks yang berbeda untuk memahami peran yang lebih dalam dari kegiatan keagamaan dalam mengatasi Bullying